Field Evaluation of a Dual Rapid Immunodiagnostic Test for HIV and Syphilis Infection in Peru. Issue 1 (January 2016) - Bristow, Claire C.; Leon, Segundo R.; Huang, Emily; Ramos, Lourdes B.; Vargas, Silver K.; Flores, Juan A.; Konda, Kelika A.; Caceres, Carlos F.; Klausner, Jeffrey D.
Abstract : Background: Integrated prevention for HIV and syphilis is warranted because both syphilis and HIV infections have evidence-based, scalable interventions using current health care mechanisms. The advent of dual rapid point-of-care tests, single devices that can detect multiple infections using the same specimen, provides the opportunity to integrate the screening of syphilis into HIV prevention programs, potentially increasing the numbers of people tested and allowing for same-day testing and treatment. The aim of our study was to evaluate the MedMira Multiplo Rapid TP/HIV Antibody Test (MedMira Inc, Halifax, Nova Scotia, Canada), a qualitative, rapid immunoassay that detects antibodies to Treponema pallidum and HIV. Methods: The reference test for comparison to the T. pallidum component of the Multiplo TP/HIV Test was the T. pallidum particle agglutination assay. For the HIV component, the reference test included a fourth-generation enzyme immunoassay with a confirmatory Western blot test. Results: The sensitivity and specificity for the HIV antibody component were 93.8% (95% confidence interval [CI], 69.8%–99.8%) and 100% (95% CI, 97.7%–100%), respectively. The T. pallidum component of the test had a sensitivity of 81.0% (95% CI, 68.1%–94.6%) and a specificity of 100% (95% CI, 97.6%–100%). Conclusions: Our study showed excellent performance of the HIV antibody component of the test and very good performance for the T. pallidum antibody component of the MedMira Multiplo Rapid TP/HIV Antibody Test, which should be considered to improve screening coverage. Use of effective dual tests will create improved access to more comprehensive care by integrating the screening of syphilis into HIV prevention programs. Abstract : We evaluated MedMira Multiplo Rapid TP/HIV Antibody Test for the simultaneous detection of HIV and syphilis infection. The dual test shows good performance in a field setting in Lima, Peru.